Quantification of coumarin and related phenolics in cinnamon samples from south India using UHPLC-ESI-QqQLIT-MS/MS method. Issue 1 (1st January 2018) - Ananthakrishnan, R.; Chandra, Preeti; Kumar, Brijesh; Rameshkumar, K. B.
ABSTRACT: The presence of coumarin, a hepatotoxic phenyl propanoid, in samples of the spice, cinnamon, procured from the market has raised food safety concerns world over. A validated, ultra-performance liquid chromatography- linear ion trap triple quadrupole mass spectrometry method was developed in the present study for the estimation of coumarin and other phenolics in authentic Cinnamomum verum bark samples and market samples from south India. Coumarin contents in authentic bark samples were in the range of 12.3 to 143.0 mg/kg, whereas the coumarin contents in samples procured from the market were up to 3462.0 mg/kg. The high content of coumarin and cinnamaldehyde in cinnamon samples procured from the market suggested possible blending with substitutes like Cinnamomum cassia barks, which possess substantial amounts of coumarin and cinnamaldehyde.